2021
DOI: 10.33314/jnhrc.v18i4.3051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perinatal Outcomes between Borderline and Normal Amniotic Fluid Index in Term Singleton Pregnancies

Abstract: Background: Amniotic fluid provides necessary fluid and growth factors for normal development of fetal lungs, cushions the umbilical cord from compression and protects the fetus. This study aims to compare the perinatal outcome between pregnancy with borderline and normal Amniotic Fluid Index that provide greatest chance for appropriate safe delivery with least maternal fetal and neonatal risk.Methods: A total of 94 singleton full term pregnant women were included in the study-at Kathmandu Model Hospital from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
3
2
Order By: Relevance
“…In contrast to the findings of the present study, based on another study that was conducted with the aim of comparing perinatal outcomes in two groups with borderline and normal AFI, adverse pregnancy outcomes, including fetal distress and hospitalization in the NICU, were not statistically significantly different between the two groups ( 7 ). However, increased NICU admission rates can be associated with fetal distress and low APGAR score ( 18 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the findings of the present study, based on another study that was conducted with the aim of comparing perinatal outcomes in two groups with borderline and normal AFI, adverse pregnancy outcomes, including fetal distress and hospitalization in the NICU, were not statistically significantly different between the two groups ( 7 ). However, increased NICU admission rates can be associated with fetal distress and low APGAR score ( 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The common method used to measure amniotic fluid volume is the use of the amniotic fluid index (AFI) in ultrasound, based on which the largest vertical amniotic fluid pocket in each of the four quadrants of the uterus is selected and then added together ( 7 , 8 ). AFI is one of the parameters used to evaluate fetal well-being, predict adverse perinatal outcomes and perform necessary interventions to improve these outcomes ( 3 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of housewife was the highest in all groups: oligohydramnios 88.7%, normal AF 91.3%, and polyhydramnios 82.0%. A Study by Bajracharya et al, (2020) disagreed with the current study and found that occupation status and education were not statistically significant with AFV. Bauserman et al,.…”
Section: Discussioncontrasting
confidence: 99%